The handbook of informal language learning - Dressman, Mark; Sadler, Randall, 1965- (Blackwell handbooks in linguistics ;, 2020)
"The Handbook of Informal Language Learning is the first handbook-length resource in the field on a growing and hugely relevant area of research in second language learning. Divided into six sections: Theorizing Informal Language Learning; Digital Language Learning; Learning through Media and Others; Cultural and Historical Cases of Informal Language Learning; Informal Learning Applications in Formal Contexts; and The Future of Informal Language Learning, this Handbook offers a comprehensive assessment of second language learning outside of formal contexts. Authored by a prominent team of international experts in their respective fields, the individual chapters of the Handbook are masterfully brought together by the highly qualified editorial team of Mark Dressman and Randall Sadler. A state-of-the-art volume in a burgeoning field, The Handbook of Informal Language Learning is written so that it is accessible to a wide audience of researchers, teacher educators, and students of foreign language education, English as an International Language (EIL), TESOL, and media and communication courses"--